2009
DOI: 10.1111/j.1939-1676.2009.0333.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Regulatory T Cells in Dogs with Cancer and Associations with Tumor Type

Abstract: Background: Regulatory T cells (Treg) have been shown to suppress antitumor immunity and often are increased in humans and rodents with cancer. However, Tregs have not been well studied in dogs with cancer and it is not known if certain tumor types are associated with increased Tregs.Hypothesis: We hypothesized that Treg percentages would be increased in dogs with cancer and that Treg percentages would be higher in dogs with certain types of cancer.Animals: The percentages and numbers of Tregs and nonregulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
52
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 45 publications
12
52
0
1
Order By: Relevance
“…Similar results have been previously reported by O'Neill et al (2009), who analysed dogs with various types of neoplasia (sarcoma, carcinoma, lymphoma and mastocytoma) and by Mitchell et al (2012) in dogs with type B lymphoma. On the other hand, other studies (Winnicka et al, 2002;Walter et al, 2006) have reported significant differences between healthy and neoplastic dogs and have attributed such differences to factors related to the tumours, suggesting that these tumours can be suppressive; however, no information on the type of suppression was provided (Winnicka et al, 2002).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar results have been previously reported by O'Neill et al (2009), who analysed dogs with various types of neoplasia (sarcoma, carcinoma, lymphoma and mastocytoma) and by Mitchell et al (2012) in dogs with type B lymphoma. On the other hand, other studies (Winnicka et al, 2002;Walter et al, 2006) have reported significant differences between healthy and neoplastic dogs and have attributed such differences to factors related to the tumours, suggesting that these tumours can be suppressive; however, no information on the type of suppression was provided (Winnicka et al, 2002).…”
Section: Discussionsupporting
confidence: 79%
“…Firstly, the way of expressing the results could be one of these factors since the relative values of CD4 + and CD8 + were transformed into absolute values (in relation to the number of lymphocytes obtained in the haemogram) (Winnicka et al, 2002). Another factor would be to analyse together data from different types of tumours, as described by O'Neill et al (2009). Lastly, patients with one type of tumour with various histological classifications and immunophenotypes, such as lymphoma, could be analysed the same way by the same analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, some authors observed a significant increase in Tregs of dogs with cancer compared to healthy dogs (O'Neill et al, 2009). Other authors found that Tregs were significantly higher in dogs with metastatic tumors than in dogs with nonmetastatic tumors (Horiuchi et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…In dogs, a number of research articles have been published based upon changes in CD4 + and Foxp3 + proportion of cells that occur in tumors (Gereda et al, 2000;Biller et al, 2007;O'neill et al, 2009;Horiuchi et al, 2009;Rissetto et al, 2010;Biller et al, 2010;Tominaga et al, 2010). A study comparing the percentage of Tregs between healthy dogs and those with diverse tumors such as round cell tumors, sarcomas and carcinomas, showed a higher Tregs expression both in peripheral blood and tumor tissue (Biller et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation